1977
DOI: 10.1007/bf01966847
|View full text |Cite
|
Sign up to set email alerts
|

Auto-modulation of release of pharmacological mediators of immediate (type I) hypersensitivity. A review

Abstract: IntroductionVarious chemical agents (pharmacological mediators) are released from sensitized tissue following exposure to specific antigen. These mediators include: histamine, serotonin, slowreacting substance of anaphylaxis, catecholamines, kallikreins and kinins, platelet activating factor, several chemotactic factors and prostaglandins. The release of a combination of these substances provides evidence for the existence of the 'Type I' anaphylactic reaction: the tissue mast cells and circulating leukocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…Theophylline has been shown to exert several actions beneficial in the treatment of bronchial asthma such as relaxation of bronchial smooth muscle, stimulation of mucociliary clearance, suppression of pulmonary oedema and inhibition of mediator release (Persson, 1980;Kaliner & Austen, 1974;Holroyde, Burka & Eyre, 1977). Andersson (1 980b) showed that aminophylline given intravenously inhibited the antigen-induced bronchial anaphylaxis independently of the mode of immunization at a concentration that did not show bronchodilator properties when tested against a histamine-induced contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Theophylline has been shown to exert several actions beneficial in the treatment of bronchial asthma such as relaxation of bronchial smooth muscle, stimulation of mucociliary clearance, suppression of pulmonary oedema and inhibition of mediator release (Persson, 1980;Kaliner & Austen, 1974;Holroyde, Burka & Eyre, 1977). Andersson (1 980b) showed that aminophylline given intravenously inhibited the antigen-induced bronchial anaphylaxis independently of the mode of immunization at a concentration that did not show bronchodilator properties when tested against a histamine-induced contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Theophylline has been shown to inhibit the release of pharmacological mediators of the immediate-type allergic reaction probably by increasing the mast cell cyclic AMP level (Kaliner & Austen, 1974;Holroyde, Burka & Eyre, 1977). Theophylline also blocks the potentiating effect of adenosine on mast cell histamine release (Marquardt, Parker & Sullivan, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…In allergic pulmonary disease, numerous chemical agents (pharmacological mediators) are released from the lung tissue by specific antigen (Austen & Orange, 1976;Piper, 1977;Holroyde, Burka & Eyre, 1977); these mediators are responsible, in part, for the clinical symptoms in obstructive lung disease. Some actions of many of these mediators on various bovine blood vessels, including the pulmonary vasculature, have been described previously (Eyre, 1971;Burka & Eyre, 1974a;1977;Holroyde & Eyre, 1975 Aviado, 1962).…”
Section: Introductionmentioning
confidence: 99%